An investigation of electrolytic surface damages and electroplated crhomium effects on fatigue behavior of high strength steel - De Amorim, Carlos Eduardo Silva [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Dos Santos Vieira, Luiz Fábio; Pigatin, Walter Luis (SAE International, 2001)
Fatigue crack initiation occurs at the surface, although sub surface nucleation has also been reported. Localized imperfections like inclusions close to surface and surface small pits can result in crack sources. Coatings are not always beneficial by fatigue point of view too. Mechanical properties of the covering material can change considerably the fatigue behavior of base metal due to residual surface stresses, to micro cracks or to hydrogen embrittlement. This paper is concerned with analysis of electrolytic etch on the fatigue resistance of a 35NCD16 high strength steel in a mechanical condition of (1760 - 1960) MPa, and analysis of electroplated hard chromium effects on the fatigue resistance in a strength condition of 989 MPa. Hardness impression was used as a reference parameter in case of electrolytic etch. In both cases, experimental data showed that fatigue strength of 35NCD16 steel was considerably reduced. Copyright © 2001 Society of Automotive Engineers, Inc.
Keywords: 35NCD16 steel; Base metals; Covering material; Crack sources; Electrolytic surface; Electroplated hard chromiums; Experimental data; Fatigue behavior; Fatigue crack initiation; Fatigue strength; Reference parameters; Strength condition; Sub-surfaces; Surface stress; Chromium; Electrolytic analysis; Fatigue of materials; High strength steel; Mechanical properties; Surfaces